2005
DOI: 10.1021/tx050068y
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Liquid Chromatography Electrospray Ionization Tandem Mass Spectrometry for the Detection and Quantitation of Benzo[a]pyrene−DNA Adducts

Abstract: A method, using HPLC combined with electrospray tandem mass spectrometry (ES-MS/MS), was developed and validated to detect and quantify the major DNA adduct resulting from exposure to the ultimate tumorigenic benzo[a]pyrene (BP) metabolite, trans-7,8-dihydroxy-anti-9,10-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene (BPDE). Calf thymus DNA was reacted with BPDE, digested enzymatically to nucleosides, and the major DNA adduct, 10-(deoxyguanosin-N2-yl)-7,8,9-trihydroxy-7,8,9,10-tetrahydrobenzo[a]pyrene (dG-BPDE), was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 28 publications
2
124
0
Order By: Relevance
“…The method development for stereoisomeric analysis of BPDE-DNA adducts takes multiple steps and labor-intensive. It often involves with the preparation of single stereoisomers of adducted nucleosides or nucleotides (which are not commercially available), and the structural and stereochemical characterization, enzymatic digestion of genomic DNA, and highly efficient and stereoselective separation and coupled sensitive detection [10,21,28]. Among these steps, the stereoselective separation of the adduct stereoisomers is most critical and tunable factor for achieving high sensitivity of detection.…”
Section: Introductionmentioning
confidence: 99%
“…The method development for stereoisomeric analysis of BPDE-DNA adducts takes multiple steps and labor-intensive. It often involves with the preparation of single stereoisomers of adducted nucleosides or nucleotides (which are not commercially available), and the structural and stereochemical characterization, enzymatic digestion of genomic DNA, and highly efficient and stereoselective separation and coupled sensitive detection [10,21,28]. Among these steps, the stereoselective separation of the adduct stereoisomers is most critical and tunable factor for achieving high sensitivity of detection.…”
Section: Introductionmentioning
confidence: 99%
“…In lung DNA, one adduct was tentatively identified as the anti-benzo [a]pyrene -7,8-diol-9,10-oxide-deoxyguanosine adduct (Culp & Beland, 1994). The identity of this adduct was confirmed by analysis of the lung DNA of female B6C3F1 mice fed a diet of coal tar from manufactured gas plant residue; however, based on the levels of this adduct, it was suggested that benzo [a]pyrene may contribute only a small fraction to the DNA adducts formed in the lung tissue of mice administered coal tar (Beland et al, 2005). Female B6C3F1 mice were fed diets of coal tar, and DNA adduct formation, cell proliferation and mutations in tumours in the K-ras, H-ras and p53 genes were determined.…”
Section: (C) Creosotementioning
confidence: 99%
“…[26,89,90]. In all of these studies there were inter-laboratory comparison of DNA samples that were modified in vitro, extracted from exposed animals and, in the case of B[a]P extracted from human tissue.…”
Section: Validation Of Dna Adduct Determination and Its Use In Risk Amentioning
confidence: 99%